(untitled) (Journal of Nepal Geological Society, 1985)
The Kulekhani Hydroelectric Project is located in Bhimphedi group of Kathmandu complex. Kalitar formation, Chisapani quartzites and Kulekhani formations are the main rock types with Palung granite massif intruded in the middle part of the area. Alluvial deposits are widely developed in the Southern part. The dam foundation consists of quartzites and schists of Kulekhani formation. The foundation rocks are weaker on both the banks. Core trench was excavated up to the level of sound rocks and foundation treatment done up to 100m depth rendering the foundation watertight.